2020
DOI: 10.3390/ijerph17207516
|View full text |Cite
|
Sign up to set email alerts
|

Selected Behavioural Factors Affecting Oral Health in Schoolchildren: Results from the Health Behaviour in School-Aged Children (HBSC) Slovak Study

Abstract: Oral diseases, particularly dental caries, affect as much as nine in 10 persons globally. Its development starts during childhood. Behavioural factors play an important role in its aetiology. The aim of the research was to analyse the prevalence of selected behavioural factors associated with dental caries in Slovak adolescents. Selected factors, such as toothbrushing less than once a day, consumption of sweets and sweetened soft drinks daily and their combination, were analysed using data from Health Behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…Many epidemiological studies have observed that the rate of dental caries was effectively controlled by enhancing the optimum oral hygiene preventive protocol [9][10][11][12][13]. Parental attitudes toward the importance of oral hygiene play a major role in the preservation of healthy children's teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiological studies have observed that the rate of dental caries was effectively controlled by enhancing the optimum oral hygiene preventive protocol [9][10][11][12][13]. Parental attitudes toward the importance of oral hygiene play a major role in the preservation of healthy children's teeth.…”
Section: Introductionmentioning
confidence: 99%
“…The average frequency of toothbrushing per day was lower in those with low educational level, the unemployed, and those living in rural areas. Another study in adolescents [ 22 ] in Slovakia showed an association between the absence of daily toothbrushing and lower socioeconomic status. In Australia [ 21 ], children who had private health insurance exhibited higher frequency of toothbrushing.…”
Section: Discussionmentioning
confidence: 99%
“…Student’s oral health knowledge was scored using a system adopted from previous studies (7,8) Oral health knowledge was determined by asking the following questions (1) periodontal disease can affect health, (2) regular tooth brush can protect tooth decay, (3) fizzy soft drinks affect the teeth, (4) use of fluorides prevent tooth decay, (5) gingivitis is a disease that makes your gums bleed, (6) causes of dental caries or proper tooth brushing can prevent dental caries (7) sugar causes tooth decay, (8) tooth decay is a disease that destroys your teeth, and (9) healthy teeth means strong and carries free teeth. Oral health practices were determined by asking the following questions: (1) frequency of brushing teeth, per day, (2) time spent for brushing in minute, (3) cleansing aid used, (4) materials used to clean teeth, (5) frequency of changing tooth brush, (6) type of toothpaste used, (7) mouth rinsing after eating, (8) clean tongue after meal or during rushing.…”
Section: Methodsmentioning
confidence: 99%
“…Moghaddam et al, showed that children’s poor oral health condition is related to lower education level of their mother and father and with lower family income (2). Children of parents who have lower education level and lower level of socio-economic status are more affected by dental caries and other oral health related problems (3).…”
Section: Introductionmentioning
confidence: 99%